A report on the practice in industry training in fish culture - De Leon, Augusto Nery
Practice in industry training occupies a unique place in curriculum of the Philippine Institute of Fisheries technology. It is one chance in a lifetime for the ambitious students to gain through their own effort knowledge or enlightenment about the vast field of fishery, fish culture in particular. During the span of six months in actual fieldwork, learners' dim eyes will undoubtedly be opened into brighter world for beyond the dream of the student. More than any other means it offers the sumptuous opportunity of observing the do's and don'ts of the fishpond management.